Arts Across Eswatini: Pedagogical Outcomes - Epilogue Jedishkem; Jesfaith Jedishkem (Recent Research Advances in Arts and Social Studies Vol. 8, 2024)
The zeitgeist of childhood is characterized by ebullience, which requires creative imaginations to accommodate and express emotional ideas, the power of arts is germane in making this happen at this epoch. Eswatini elementary curriculum formally boarded the creative artistic train in 2018, the competency-based expressive arts as a core subject started as a pilot research, implemented in the precocious stage of grade one to advance skill and aptitude at an early age; and then progressed to upper grades. This is to challenge learners to meet high but realistic expectations geared toward articulate competencies to meet sustainable development goals. National Curriculum reviews investigated outcomes and experiences of the refined subject, as reported by Mamba and Zulu in Times of Eswatini, they stressed the need for the country to embrace the arts with all serosity as it is quintessential in bridging the gap in joblessness in the country, a national focus [1,2]. Jedishkem and co-authors concurred, that regardless of a college qualification, the arts are dependent variables needed for success in the current world economy [3]. Recognizing and nurturing creative growth aesthetically is relevant to skill development and enhances holistic education. The study was conducted over the course of over fourteen thirty-minute periods in mid-2023, detailed research was carried out in a singular subject area by datum recording first-hand data on classroom phenomena on the outcomes of Expressive Arts from seven elementary public schoolrooms involving over 350 learners and 7 pre-service educators in Eswatini. Instructors’ training and knowledge of the arts were probed, besides reflections on art pedagogy. Adept educators communicated their pleasure in teaching the subject, unfortunately, the inept deemed it a fifth wheel. They neither take it seriously nor look forward to artsy sessions since there is a wide knowledge skill gap and social competencies. Introduction to the art variants of dance, drama, music, and visual art enabled learners to be inspired to perform before audiences or even be part of an audience having the chance to exhibit their creative abilities. Guided by the textbooks they were exposed to techniques relevant to specific art trajectories that deepened their understanding of themselves, others, and the world at large fostering imagination despite the extrapolated demerits of inexpert instructors amidst unresourceful dire straits.